Pengaruh Tingkat Pendapatan Petani Kelapa Sawit Terhadap Kesejahteraan Menurut Perspektif Islam (Studi di Desa Merlung Kecamatan Merlung Kabupaten Tanjung Jabung Barat) - Ahmad Wahyudi; Sissah Sissah; Laily Ifazah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the effect of income on welfare and to compare the level of welfare between independent smallholders and oil palm plasma farmers according to the welfare theory put forward by Imam Ghozali (Study in Merlung Village, Merlung District, West Tanjung Jabung Regency). The research method used in this research is quantitative-descriptive, namely research that emphasizes objective phenomena and is studied through observation, questionnaires, documentation, and documents related to this subject matter. The data analysis method in this study used the SPSS version 26 statistical test tool. The results of this study indicate that the income variable partially affects the welfare variable because the t count value is greater than t table (2851 > 1.668) and a significance value of 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected, meaning that the income variable has a significant effect on the variable welfare. This result means that if the income variable increases, then the welfare variable for oil palm farmers will also increase. Based on the average score of the income variable in the statements of independent smallholders and plasma smallholders it is known that it is 3.47: 3.63 which means that overall oil palm smallholders have income that is in the good/high category. Meanwhile, the average score of the welfare variable based on the indicators of Imam Ghozali's theory is known to be 3.37: 3.66, which means that the welfare level of plasma farmers is better than that of independent smallholders.